THE PROFILE OF SPECIFIC ANTIBODIES TO SARS-COV-2 IN RESIDENTS OF THE CENTRAL AND EASTERN REGIONS OF UKRAINE - Avetikov, D.S.; Ananieva, M.M.; Loban, G.A.; Faustova, M.O.; Skikevych, M.G.; Chumak, Yu.V.; Ivanytska, O.S. (World of Medicine and Biology, 2022)
Determination of the level of antibodies in individuals living in certain regions provides insight into the epidemiology of the infection and is crucial for the development of strategies to reduce the spread of COVID-19. The study analyzed the results of IgM and IgG tests for the SARS-CoV-2 virus in 7142 residents of eastern and central regions of Ukraine from July 2020 to January 2021. Patients' visits to COVID-19 for IgM and IgG mainly occurred in the autumn-winter period of 2020–2021, confirming the seasonality of the disease. The most popular test among residents of Poltava and Donetsk regions was the test for IgM immunoglobulins, and the vast majority of results were negative. As of January 2021, the number of people who had IgG antibodies to the pathogen COVID-19, among those surveyed approached 50 % in both Poltava and Donetsk regions.
Keywords: COVID-19; SARS-CoV-2; antibodies; IgM; IgG